Long-Term Cost-Effectiveness of Severity-Based Triaging for Large Vessel Occlusion Stroke - Gao, Lan; Moodie, Marj; Yassi, Nawaf; Davis, Stephen M.; Bladin, Christopher F.; Smith, Karen; Bernard, Stephen; Stephenson, Michael; Churilov, Leonid; Campbell, Bruce C. V.; Zhao, Henry (Frontiers in Neurology, 2022)
Background and purpose Pre-hospital severity-based triaging using the Ambulance Clinical Triage For Acute Stroke Treatment (ACT-FAST) algorithm has been demonstrated to substantially reduce time to endovascular thrombectomy in Melbourne, Australia. We aimed to model the cost-effectiveness of an ACT-FAST bypass system from the healthcare system perspective. Methods A simulation model was developed to estimate the long-term costs and health benefits associated with diagnostic accuracy of the ACT-FAST algorithm. Three-month post stroke functional outcome was projected to the lifetime horizon to estimate the long-term cost-effectiveness between two strategies (ACT-FAST vs standard care pathways). For ACT-FAST screened true positives (i.e. screened positive and eligible for EVT), a 52 mins time saving was applied unanimously to the onset to arterial time for EVT, while 10 mins delay in thrombolysis was applied for false-positive (i.e. screened positive but was ineligible for EVT) thrombolysis-eligible infarction. Quality-adjusted life year (QALY) was employed as the outcome measure to calculate the incremental cost-effectiveness ratio (ICER) between the ACT-FAST algorithm and the current standard care pathway. Results Over the lifetime, ACT-FAST was associated with lower costs (-$45) and greater QALY gains (0.006) compared to the current standard care pathway, resulting in it being the dominant strategy (less costly but more health benefits). Implementing ACT-FAST triaging led to higher proportion of patients received EVT procedure (30 more additional EVT performed per 10,000 patients). The total Net Monetary Benefit from ACT-FAST care estimated at A$0.76 million based on its implementation for a single year. Conclusions An ACT-FAST severity-triaging strategy is associated with cost-saving and increased benefits when compared to standard care pathways. Implementing ACT-FAST triaging increased the proportion of patients who received EVT procedure due to more patients arriving at EVT-capable hospitals within the 6-h time window (when imaging selection is less rigorous).